The dawn of digital public health in Europe: Implications for public health policy and practice - Brian Li Han Wong; Laura Maaß; Alice Vodden; Robin van Kessel; Sebastiano Sorbello; Stefan Buttigieg; Anna Odone (Elsevier, 2022)
Summary: The COVID-19 pandemic has highlighted the importance of digital health technologies and the role of effective surveillance systems. While recent events have accelerated progress towards the expansion of digital public health (DPH), there remains significant untapped potential in harnessing, leveraging, and repurposing digital technologies for public health. There is a particularly growing need for comprehensive action to prepare citizens for DPH, to regulate and effectively evaluate DPH, and adopt DPH strategies as part of health policy and services to optimise health systems improvement. As representatives of the European Public Health Association's (EUPHA) Digital Health Section, we reflect on the current state of DPH, share our understanding at the European level, and determine how the application of DPH has developed during the COVID-19 pandemic. We also discuss the opportunities, challenges, and implications of the increasing digitalisation of public health in Europe.